TRANSFORMATION OF DEVELOPMENT TOWARDS INDEPENDENT VILLAGE IN SEKAPUK VILLAGE, UJUNGPANGKAH DISTRICT, GRESIK REGENCY - Ahmad Irfan Muzakki; Lukman Arif (DIA: Jurnal Administrasi Publik, 2021)
The commitment of the Jokowi – Jusuf Kalla government in developing villages is stated in the third the Nawa Cita which has been mandated to “Build Indonesia from the periphery by strengthening regions and villages within the framework of a unitary state”. The purpose of this study is to describe the efforts made by the government Sekapuk Village in the transformation of development towards an independent village and to describe the inhibiting and driving factors during the process of becoming an independent village. Data collection techniques in this study used interviews, observation, and documentation, in which the data were analyzed descriptively qualitatively. The informant withdrawal technique uses a purposive technique based on criteria. All data were examined for data validity using source and data triangulation techniques and were analyzed through the process of data reduction, data presentation, and conclusion drawing. The results of this study indicate that in the efforts made, the Sekapuk Village government is in the transformation of development towards an independent village through potential mapping, coaching, and mentoring, building synergies, and implementing village governance into a modern organization. Able to realize Sekapuk Village into an Independent Village. While the inhibiting factors in the transformation of development are in the form of rejection from the community, the problem of the lack of development funds, and the location of the village which is far from urban areas. the driving factors in the transformation of development in the form of a strong will from the community, the desire to reduce the number of unemployed, and the desire to reduce the problem of slums.